Understanding the challenges and the opportunities associated with leadership development for students of higher learning institution in Sabah, Malaysia - Romzi Ationg; Mohd. Sohaimi Esa; Irma Wani Othman; Mohd Kamal Mohd Shah; Muhammad Safuan Yusoff; Habibah @ Artini Ramlie; Saifulazry Mokhtar (Global Academic Excellence, 2021)
The presence of effective leadership is always vital for the successful attainment of common goals. Given that the students of HLIs are the potential leaders of any organization or society in the future, leadership development programs/courses generally required in HLIs. Accordingly, in an effort to ensure the Higher Learning Institutions graduates well equipped with effective leadership knowledge and skill, the HLIs in Sabah is offering leadership development programs/courses. Despite that, however, many remain clueless of what exactly are the challenges and opportunities associated with these leadership development programs/courses. By applying a qualitative approach through the examination of information gathered from various sources such as books, journals, and media reports, the paper presents a discussion on the challenges and opportunities associated with leadership development programs/courses for students of HLIs in Sabah, Malaysia. The findings are expected to contribute to the systematic understanding of challenges and opportunities of leadership development programs/courses for students of HLIs, thus led to the enrichment of existing leadership development programs in HLIs.